2019
DOI: 10.1038/s41409-019-0469-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of the loss of chromosome 7q on outcomes of patients with myelodysplastic syndromes treated with allogeneic hematopoietic stem cell transplantation

Abstract: Clinical impact of the loss of chromosome 7q on outcomes of patients with myelodysplastic syndromes treated with allogeneic hematopoietic stem cell transplantation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…Recent studies have suggested that der(1;7) patients with myeloid neoplasms may have a favorable prognosis. [14]. In our study, AML patients with der(1;7) had a better OS and LFS than those with -7/del(7q), a trend that was similar to previous studies on MDS patients with der(1;7).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Recent studies have suggested that der(1;7) patients with myeloid neoplasms may have a favorable prognosis. [14]. In our study, AML patients with der(1;7) had a better OS and LFS than those with -7/del(7q), a trend that was similar to previous studies on MDS patients with der(1;7).…”
Section: Discussionsupporting
confidence: 91%
“…Itonaga et al. reported that MDS patients with isolated der(1;7) had better transplant outcomes than those with isolated ‐7/del(7q), regardless of disease status [ 14 ]. In our study, AML patients with der(1;7) had a better OS and LFS than those with ‐7/del(7q), a trend that was similar to previous studies on MDS patients with der(1;7).…”
Section: Discussionmentioning
confidence: 99%
“…More relevant studies are needed to address differences in OS between sole der(1;7) and sole −7 in MDS. Considering the survival characteristics of −7 may be similar to those of −7/del(7q), as −7 accounted for around 80% of −7/del(7q), 43 we included another study finding that sole der(1;7) had significantly longer OS and relapse time after transplantation than sole −7/del(7q) 31 . Combining data from the three studies, both fixed and random‐effects models corroborate better prognosis for sole der(1;7) compared to sole −7.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data collected for analyses included patient age at transplantation, patient sex, disease subtype according to the FAB classification, cytogenetic risk classification according to International Prognostic Scoring System (IPSS), 23 the year of allo-HSCT, time from MDS diagnosis to transplantation, PS according to the Eastern Cooperative Oncology Group criteria at allo-HSCT, the type of donor source according to previous studies, [24][25][26][27][28] data at the last follow-up, and the date and cause of death. Conditioning regimens were classified as myeloablative (MAC) and reduced-intensity (RIC) according to the established criteria.…”
Section: Definitionsmentioning
confidence: 99%
“…The diagnosis and clinical grading of acute and chronic GVHD were performed according to standard criteria. 31,32 Due to missing data on IPSS components at allo-HSCT in TRUMP, the disease risk was stratified according to the FAB classification as previously reported 24,26,33,34 ; the early disease status group contained patients whose subtype remained as refractory anemia (RA) or RA with ring sideroblasts (RARS) from diagnosis to transplantation. Patients diagnosed with RAEB or RAEB-t at any time between diagnosis and transplantation were considered to be an advanced disease status.…”
Section: Definitionsmentioning
confidence: 99%